SURVEI METODE SELF POTENTIAL MENGGUNAKAN ELEKTRODA POT BERPORI UNTUK MENDETEKSI ALIRAN FLUIDA PANAS BAWAH PERMUKAAN DI KAWASAN BATURADEN KABUPATEN BANYUMAS JAWA TENGAH - Sehah Sehah; Sukmaji Anom Raharjo (Lambung Mangkurat University Press, 2011)
Self Potential research has been done in the area of geothermal prospectsof Slamet Volcano, with locations is at around the hot water sources of PancuranTujuh Baturaden, District of Banyumas, Central Java. Tools used in this study wereporous pot electrodes and digital milivoltmeter that have very high input impedance.Dimension of research area are 24 x 24 square meters, with the number ofmeasurement points are 112 point. The electrode configuration used is the fixedmodel that is by keeping one electrode fixed at the reference point, while the otherelectrode moved at any interval in accordance with the direction of trajectory in theresearch area. According to the results obtained is known that the highest potentialdata obtained is -2.20 mV, the lowest data is -40.83 mV, and then the average data is-16.40 mV. According to the contour map of iso-potential obtained is known that thestudy area is a conductive zone, which probably contains of sulfide minerals in thesubsurface hot fluid. This is indicated by the low value of the measured self potential(its value are negative). According to qualitative and quantitative interpretation, knownthat the flow of subsurface hot fluid in following the change of research areatopography and self potential anomalies. The subsurface hot fluid in research area ispredicted flow from southern to northern.